Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jvim.15787
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of the effect of metoclopramide, erythromycin, and exenatide on solid‐phase gastric emptying in healthy cats

Abstract: Background Available data on the effect of gastrointestinal motility‐modifying drugs in cats are limited. Most recommendations for drug usage and dosage are based on collective clinical experience. Objectives To assess the effects of metoclopramide, erythromycin, and exenatide on gastric emptying (GE) and gastric motility in comparison to placebo. We hypothesized that metoclopramide and erythromycin would have prokinetic gastric effects, whereas exenatide would prolong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 43 publications
3
15
1
Order By: Relevance
“…Even though no precise data are available on how fast A. abstrusus L3 penetrate the intestinal mucosa, it can be assumed that the whole infection dose is assured as the mean half-time of gastric emptying after liquid meals is supposed to be < 80 min [ 41 ]. In addition, gastric emptying is accelerated by metoclopramide [ 42 ]. In another study, one cat vomited 23 min after inoculation of 800 L3, but still harboured 36 worms in the dissected half of the lung without re-inoculation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though no precise data are available on how fast A. abstrusus L3 penetrate the intestinal mucosa, it can be assumed that the whole infection dose is assured as the mean half-time of gastric emptying after liquid meals is supposed to be < 80 min [ 41 ]. In addition, gastric emptying is accelerated by metoclopramide [ 42 ]. In another study, one cat vomited 23 min after inoculation of 800 L3, but still harboured 36 worms in the dissected half of the lung without re-inoculation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metoclopramide has questionable central antiemetic effects in cats, but when administered as a constant rate infusion (CRI), metoclopramide increases gastric emptying and decreases gastric atony. [136][137][138][139] One study suggested a contraindication to the use of metoclopramide because of dopamine antagonism in cats with pancreatitis, but no clinical studies have confirmed such a contraindication. 127 Compounded cisapride is an effective PO prokinetic in cats and is the treatment of choice for delayed gastric emptying.…”
Section: Management Of Acute Pancreatitismentioning
confidence: 99%
“…Although limited, data in cats demonstrate that GLP-1RAs generally have similar effects to those seen in human patients and might be useful in treating feline DM (9)(10)(11)(12)(13)(14)(15)(16). Feline obesity, formally classified as a disease, is also major health concern (17).…”
Section: Introductionmentioning
confidence: 99%